Empowering Rural Ecotourism: Women's Village Organizations and Entrepreneurial Development in Golaghat, Assam - Mr. Atul Saikia, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This study explores the transformative role of women's village organizations in promoting rural ecotourism and entrepreneurial development in Golaghat, Assam. By focusing on Village Level Organizations (VLOs) of Self-Help Groups (SHGs), it examines how eco-tourism initiatives can empower women economically and socially. The research highlights the types of entrepreneurial activities women engage in within the eco-tourism sector and assesses the impact of these ventures on local communities. Through detailed case studies of successful women-led ecotourism projects in Jugibill and the Children & Water Sports Park, this study demonstrates the significant contributions of women to sustainable tourism development. It underscores the importance of VLOs in providing critical support, including training, funding, and networking opportunities, which are essential for the success of these initiatives.